THE USE OF ICT BY FARMERS TO ENHANCE THEIR PRODUCTIVITY AND MARKETING THEIR PRODUCE IN INDONESIA, THE PHILIPPINES AND THAILAND - Kaewprasert, Oradol (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2018)
The use of Information Communication Technology (ICT) in farming and the marketing of produce is slowly increasing, though the progress has been uneven across different nations. The aims of this study were to determine (1) How the farmers use ICT; (2) How ICT is used by the farmers enhance their Productivity; and (3) How ICT is used by farmers to improve their marketing strategies. The study employed in-depth interviews with farmers in Indonesia, The Philippines and Thailand using interview guidelines by means of closed ended and open-ended questions. The data collected were analyzed using both descriptive and quantitative methods. The research found that farmers in the three countries are integrating ICT in their lives, the level of ICT used to enhance productivity and marketing ranges from low to high in Indonesia, The Philippines and Thailand respectively. The findings further revealed that the farmers still use traditional methods and traditional media to gain information about cultivation and to manage their markets. The study reflected that more farmers are using ICT to help with their cultivation and marketing. Using ICT helps farmers to gain information to develop their produce, reduce the role of middleman and create chances for the producers and the consumers to meet and learn about supply and demand. Organic and high-quality produced farming attracts buyers directly to farms.